2001
DOI: 10.1080/01485010151096441
|View full text |Cite
|
Sign up to set email alerts
|

LETHAL DOSE AND REPRODUCTIVE PARAMETERS OFp-NONYLPHENOL IN RATS

Abstract: Male reproductive abnormalities may be due to an increased level of maternal estrogens affecting the developing fetus. Man is exposed to environmental estrogens in multiple ways: diet, drinking water, air, and skin, para-Nonylphenol (p-NP), an alkylphenol, has estrogenic properties. This study was performed to evaluate the potency and workable concentrations before reproductive tests could be performed. The oral LD50 (median lethal dose) value for rats was 1475 mg/kg. For both males in the reproductive test th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Animals were gavaged daily during the prepubertal stage from GD 23 to GD 35 with NP (50, 150, and 450 mg/kg/day), DBP (50, 150, and 450 mg/kg/day), and a combination of NP and DBP (50+50, 150+150, 450+450 mg/kg/day) dissolved in laboratory-grade corn oil at a volume corresponding to 5 mL/kg bw. A previous study demonstrated that the lethal dose 50 (LD50) of NP for rat was 1475 mg/kg [22] and an oral dose of 500 mg/kg/day of DBP to the rat dam during GD14–18 would be approximately half of the total effective dose which produces a 50% incidence (ED 50 ) of epididymal agenesis [23]. Therefore the highest concentration was 450 mg/kg/day for NP and DBP, respectively, and the dose of NP vs. DBP in the mixture was also at a fixed ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Animals were gavaged daily during the prepubertal stage from GD 23 to GD 35 with NP (50, 150, and 450 mg/kg/day), DBP (50, 150, and 450 mg/kg/day), and a combination of NP and DBP (50+50, 150+150, 450+450 mg/kg/day) dissolved in laboratory-grade corn oil at a volume corresponding to 5 mL/kg bw. A previous study demonstrated that the lethal dose 50 (LD50) of NP for rat was 1475 mg/kg [22] and an oral dose of 500 mg/kg/day of DBP to the rat dam during GD14–18 would be approximately half of the total effective dose which produces a 50% incidence (ED 50 ) of epididymal agenesis [23]. Therefore the highest concentration was 450 mg/kg/day for NP and DBP, respectively, and the dose of NP vs. DBP in the mixture was also at a fixed ratio.…”
Section: Methodsmentioning
confidence: 99%